2018
DOI: 10.15446/acag.v67n1.59272
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of molybdenum enhanced quality and yield of crispleaf lettuce (Lactuca sativa L., cv. Grand Rapids)

Abstract: ResumoA aplicação foliar de molibdênio (Mo) pode melhorar a absorção de N das plantas e aumentar a produtividade e a qualidade da hortaliça comercializada. Este estudo foi realizado para avaliar o efeito da aplicação foliar de molibdênio na absorção de nitrogênio e na produtividade da alface crespa (Lactuca sativa L., cv. Grand Rapids) cultivado no período de primavera-verão. O experimento foi realizado em Ourinhos (SP), durante os meses de outubro de 2013 a janeiro de 2014. Os tratamentos constituíram da apli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
1
5
0
4
Order By: Relevance
“…The foliar spray of Mo at the rate of 0.025 per cent or 0.050 per cent had increased all the 3 root parameters followed by soil application of Mo and seed treatment. Foliar spray of Mo had increased the dry matter by 3 to 4 times, root length by 2.5 times and volume by 2 times indicating the importance of foliar spray of Mo in root proliferation and dry product.This data is in accordan findings of [13].…”
Section: Effect Of Molybdenum On Dry Matter Production (Dmp) On Shootsupporting
confidence: 92%
“…The foliar spray of Mo at the rate of 0.025 per cent or 0.050 per cent had increased all the 3 root parameters followed by soil application of Mo and seed treatment. Foliar spray of Mo had increased the dry matter by 3 to 4 times, root length by 2.5 times and volume by 2 times indicating the importance of foliar spray of Mo in root proliferation and dry product.This data is in accordan findings of [13].…”
Section: Effect Of Molybdenum On Dry Matter Production (Dmp) On Shootsupporting
confidence: 92%
“…The present findings are concordant with previous studies, where Mo supplementation increased the Mo concentration in ‘ Le-Conte ’ pear [ 37 ], grapes (cv. Merlot) [ 38 ], peanut [ 39 ] and lettuce [ 40 ]. Togay et al [ 41 ] also reported the enhanced concentration of Fe, P, Mn, Cu and Mo in lentil ( Lens culinaris Medic.)…”
Section: Discussionmentioning
confidence: 99%
“…Resultados similares foram obtidos por Steiner et al (2018), observando aumento de 33% do peso de folhas frescas quando aplicado Mo via fertilizante foliar. Neste trabalho, constatou-se como melhores resultados para MSF o valor de 33,96 g planta -1 para dose de 1,67 L ha -1 da combinação Spin ® + Fence ® , 20,09 g planta -1 para dose de 1,35 L ha -1 de Fence ® e 24,15 g planta -1 para dose 2,22 L ha -1 de Spin ® (Figura 1).…”
Section: Resultsunclassified
“…O fertilizante Spin, mesmo com menor concentração de elementos quando comparado ao Fence, demonstrou maior valor de MSF, isso provavelmente ocorreu devido ao elemento Mo participar de sua formulação. Steiner et al (2018) observou aumento de 28% de peso seco de folhas em tratamentos com Mo quando comparados a testemunha sem Mo.…”
Section: Resultsunclassified
See 1 more Smart Citation